2018
DOI: 10.5812/iranjradiol.59022
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-Rater Reliability of Ultrasound in Plantar Fascia Thickness Measurement

Abstract: Background: Plantar fascia is a thick connective tissue on the plantar side of the foot, which provides the normal shape of the longitudinal arch. Plantar fasciitis is an inflammation on the medial tuberosity of calcaneus on the inferior side that may cause heel pain. Imaging plays an important role in the diagnosis of heel pain. Ultrasonography has been recognized as an effective imaging tool for assessing plantar fascia thickness, monitoring the effect of different interventions and guiding therapeutic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The relative reliability of thickness and echogenicity measurement of the plantar fascia was proven to be high (interclass correlation coefficient, ICC = 0.88) [401]. Good reproducibility was also found (intra-and interrater reliability, ICC > 0.821, ICC> 0.849) [402], as well as good agreement between an experienced and a novel sonographer [403]. In another study the intra-tester reliability was shown to significantly surpass the inter-tester reliability in plantar fasciitis (0.89 vs. 0.61, respectively) [404].…”
Section: Clinical Applicationmentioning
confidence: 86%
“…The relative reliability of thickness and echogenicity measurement of the plantar fascia was proven to be high (interclass correlation coefficient, ICC = 0.88) [401]. Good reproducibility was also found (intra-and interrater reliability, ICC > 0.821, ICC> 0.849) [402], as well as good agreement between an experienced and a novel sonographer [403]. In another study the intra-tester reliability was shown to significantly surpass the inter-tester reliability in plantar fasciitis (0.89 vs. 0.61, respectively) [404].…”
Section: Clinical Applicationmentioning
confidence: 86%
“…It is meant to provide stability and support to the medial arch of the foot and also acts as a dynamic shock absorber during walking and running. [1][2][3][4][5][6] Due to the constant exposure to mechanical load and trauma it is very prone to traumatic injuries, microtears and subsequent development of plantar fasciitis. [2][3][4][5][6][7] Plantar fasciitis is an idiopathic condition which is the most common cause of heel pain.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Due to the constant exposure to mechanical load and trauma it is very prone to traumatic injuries, microtears and subsequent development of plantar fasciitis. [2][3][4][5][6][7] Plantar fasciitis is an idiopathic condition which is the most common cause of heel pain. According to the published reports it predominantly affects individuals between the ages of 40-60 years.…”
mentioning
confidence: 99%
See 2 more Smart Citations